Atlas quốc gia Việt Nam - Nguyễn, Văn Chiển (2011)
Tác giả: Nguyễn Văn Chiển, GS,NGND; Nguyễn Thơ Các; Nguyễn Can; Nguyễn Trần Cầu; và những người khác -- Từ khóa: Atlat quốc gia; Bản đồ quốc gia; Việt Nam